Empowering Women: A Reflection on Protecting Against Dating Violence In the Indonesian Context - Ani Purwanti; Zahroh Shaluhiyah; Bagoes Widjanarko; Aga Natalis (Qubahan Academic Journal)
This research delves into the prevalence of dating violence among unmarried women in Indonesia, shedding light on the challenges faced by adolescents in romantic relationships. The study reveals that a substantial portion of women aged 15 to 64, specifically 33.4%, have experienced instances of physical and sexual violence throughout their lives. Notably, sexual violence constitutes a significant share of reported incidents at 34.4%, surpassing physical violence, which accounts for a comparatively lower proportion of 19.6%. The prevalence of sexual violence emerges as a critical concern, demanding focused attention. The findings underscore the urgency for clear legislation addressing violence against women and advocate for the implementation of a comprehensive global strategy to tackle this pervasive issue. Recognizing the alarming statistics, it is imperative to enact and enforce laws that explicitly condemn violence against women, ensuring the safety and well-being of the female population. Moreover, a concerted global effort is essential to address the root causes of dating violence, promoting awareness, education, and prevention. This study serves as a call to action, urging policymakers, activists, and communities to work collaboratively in fostering an environment where women can thrive without fear of violence. By addressing the issue comprehensively, from legal frameworks to societal attitudes, we can pave the way for a safer and more equitable future for women in Indonesia and beyond.